MICROBIOLOGICAL ASSESSMENT OF FECAL CONTAMINATION IN THE RIVER WATERS OF THE VOGHJI RIVER CATCHMENT BASIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Quantitative parameters of total and fecal coliform, as well as Escherichia coli bacteria in the river waters of the Voghji River catchment basin were investigated to characterize fecal contamination in the investigated watershed basin. Water samples for microbial analyses were collected from the Voghji River and its Geghi, Norashenik and Vachagan tributaries in 2016, 2017 and 2020. The results of the study revealed the distribution, potential sources and environmental risks of fecal contamination in the Voghji River catchment basin.
Keywords: rivers; fecal indicator bacteria; contamination; environmental hazards